Enhanced Survival of the Cyanobacterium Oscillatoria terebriformis in Darkness under Anaerobic Conditions - Richardson, Laurie L. (1987)
Oscillatoria terebriformis, a thermophilic cyanobacterium, maintained viability in darkness under anaerobic conditions by fermenting exogenous glucose or fructose to lactic acid. The time period of survival was greatly extended when the environmental redox potential was lowered by the addition of sodium thioglycolate or titanium(III) citrate. When exposed to aerobic conditions in darkness, many trichomes underwent lysis in 6 h, and death of all cells occurred in 2 to 3 days. The endogenous aerobic respiration rate was high, and the limited dark aerobic survival period appeared to be due to depletion of stored glycogen. Fructose or glucose did not support or increase aerobic respiration in darkness or lengthen aerobic survival time. Enhanced survival of O. terebriformis in darkness under anaerobic, reducing conditions correlates well with the natural nighttime position of this species within sulfide-rich microbial mats associated with hot springs of western North America.